Persistent high blood urea nitrogen level is associated with increased risk of cardiovascular events in patients with acute heart failure. (27th June 2017) - Jujo, Kentaro; Minami, Yuichiro; Haruki, Shintaro; Matsue, Yuya; Shimazaki, Kensuke; Kadowaki, Hiromu; Ishida, Issei; Kambayashi, Keigo; Arashi, Hiroyuki; Sekiguchi, Haruki; Hagiwara, Nobuhisa
Abstract: Aims: The association between kinetics of blood urea nitrogen (BUN) levels in hospital and cardiovascular outcomes in patients with acutely decompensated congestive heart failure (HF) is unclear. We aimed to estimate the impact of changes in BUN level during hospitalization on clinical prognosis in patients with acute HF. Methods and results: A total of 353 consecutive patients that were urgently hospitalized due to acutely decompensated HF and discharged alive were divided into four subgroups depending on their BUN level at admission and discharge, using a cut‐off level of 21.0 mg/dL. Among 206 patients with high baseline BUN level, 46 (22%) and 160 (78%) had normal and persistent high BUN levels at discharge, respectively. In contrast, of the 147 patients with normal baseline BUN level, 55 (37%) and 92 (63%) had high and normal BUN levels at discharge, respectively. During the observational period after discharge, Kaplan–Meier analysis showed the highest rate of combined outcome of cardiovascular death and HF readmission in patients with persistent high BUN (log‐rank test: P < 0.001). After adjustment for comorbidities, the hazard ratio for a combined outcome was significantly lower in patients with normalized BUN level compared with those with persistent high BUN (hazard ratio 0.48, 95% confidence interval 0.23–0.99, P = 0.049). Conclusions: Persistent high BUN levels in hospital are associated with an increased risk of cardiovascular death and HF readmission. Normalization of BUN levels during hospitalization may be associated with long‐term clinical outcomes.